Chapter 3 Curating Enslavement and the Colonial History of Denmark The 2017 centennial - Andersen, Astrid Nonbo (Taylor & Francis, 2020)
March 31, 2017 marked the centenary of the transfer of the Danish colony-the Danish West Indies (today's US Virgin Islands)-to the US. During the 100 years that had passed, the history had only occasionally been revisited in Danish public debate and history books-often shaped as a postcolonial nostalgic longing for what was perceived as a paradise lost. Even less often had the history of the Danish West Indies been the topic of museum exhibitions. However, the centenary sparked an unprecedented interest in the colonial past, unfolding in both public debate and nearly 30 special exhibitions all around the country on various topics related to the history of colonialism and enslavement. Instead of nostalgic longing, the questions often raised in these exhibitions were about the aftereffects in terms of continued colonialism in the Virgin Islands, racism, and global inequality. The museums involved ranged from small private collections to some of the largest state museums in and around the capital. Building on interviews with many of the curators involved, this chapter considers the challenges faced by museums that were often driven by a twofold ambition to create exhibitions that aligned with the wishes and feelings of descendant communities of enslaved Africans and that were able to engage an ethnic Danish audience with low prior awareness of the subject to arrive at new insights into the topic. These dual ambitions sometimes came under pressure from the political debate in the country.